SPECIES RICHNESS AND MICROHABITATS OF SPIDERS IN CAVES OF AGUSAN DEL SUR, PHILIPPINES - MAANDIG, RADONNA JESSAH CHRISTY L.; NUÑEZA, OLGA M.; DUPO, AIMEE LYNN B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Spiders are widely distributed in a variety of habitats. However, spider fauna in caves of Agusan del Sur has not been widely studied. This study aimed to determine the species richness and microhabitats of spiders belonging to 12 families in the caves of Agusan del Sur. Eight caves in three municipalities and one city in Agusan del Sur were surveyed on June 24 to July 10, 2015. A combination of vial tapping and handpicking methods was done to collect specimens. Forty-eight species of spiders were documented in the eight caves of Agusan del Sur. Agpan Cave had the highest species richness (S=19) and abundance (43.16%) which is attributed to the presence of guano deposit. Five spider microhabitats were identified. Family Sparassidae occupied all five cave microhabitats, while the family Araneidae was found on both rock surfaces and shrubs. The wall of the cave had the highest species richness of spiders. Guano deposit and habitat structures appear to be the major factors for the species richness of spiders and the continuation of the food chain in caves.